(untitled) (Książnica Śląska, 2025)
The author describes a unique album from the collection of the Biblioteka Śląska in Katowice, containing archival photographs by Katowice photographer Stefan Pierzchalski. The photographs show industrial plants of Upper Silesia, including mines with mining shafts, steelworks, coking plants and power plants. The album was probably created after 1922, and the prints pasted into it are sometimes the only preserved photographs of industrial plants of that time.